Le Diable au xxe siècle - Jordi Luengo López (Cahiers de Civilisation Espagnole Contemporaine)
At the dawn of the past century, the diffusion of the character of Mephistopheles, conceived as the modern evolution of the image of Satan, was an extraordinarily important social and cultural phenomenon from the perspective of spreading the Christian faith within the collective imaginary. In Spain, the press was fuelled by the terror of the Great War to drive the Devil from his throne of evil, thus turning him into an individual whose arts adjusted to the modern period and leaving his evil halo to the human being. All the same, as early as the decline of the nineteenth century and the height of the Belle Époque, and during the twenties and the Spanish Second Republic, the literaturisation that was made of the devil revolutionised the ideas of the Bourgeoisie and the people of the time since newspapers were much closer to people than even the Church. In this way, the press was capable of making men and women lose their fear of Satan – fear that had been instilled by Christian dogmas – to start sympathising with Mephistopheles, a character which understood the misfortunes and joys of their lives much better.